Bimetallic Janus Nanocrystals: Syntheses and Applications. Issue 1 (17th October 2021) - Qiu, Jichuan; Nguyen, Quynh N.; Lyu, Zhiheng; Wang, Qiuxiang; Xia, Younan
Abstract: Bimetallic Janus nanocrystals have received considerable interest in recent years owing to their unique properties and niche applications. The side‐by‐side distribution of two distinct metals provides a flexible platform for tailoring the optical and catalytic properties of nanocrystals. First, a brief introduction to the structural features of bimetallic Janus nanocrystals, followed by an extensive discussion of the synthetic approaches, is given. The strategies and experimental controls for achieving the Janus structure, as well as the mechanistic understandings, are specifically discussed. Then, a number of intriguing properties and applications enabled by the Janus nanocrystals are highlighted. Finally, this article is concluded with future directions and outlooks with respect to both syntheses and applications of this new class of functional nanomaterials. Abstract : Bimetallic Janus nanocrystals feature a side‐by‐side arrangement of two distinct metals divided by a heterogeneous interface. This unique structure allows one to present both metals on the same particle while tailoring the plasmonic coupling and electronic interaction between them, making the structure particularly viable for plasmonic, catalytic, and photocatalytic applications.